Turbulent fluxes and tide measurements from a coastal lagoon in the Gulf of California - Lidia Irene Benítez-Valenzuela; Zulia Mayari Sanchez-Mejia; Crhistian Anibal Silva-Ontiveros; Aylin Barreras-Apodaca (PANGAEA, 2020)
The coastal lagoon “Estero El Soldado” is a Ramsar site (no. 1982) and Natural Protected Area managed by the Sonora Ecology and Sustainable Development Commission (CEDES). In this coastal lagoon, we have installed a monitoring station that includes an eddy covariance system (EC), meteorological, and water instruments since June 2018, and we contribute to the MexFlux community. The project aims to understand better energy, water, and carbon exchange in the water-air continuum. At this site, seagrass grows during the winter-spring months (December-June). The data presented here is from 2019. Funding sources for this project at ITSON: Mexico extquotesingles National Council for Science and Technology (Consejo Nacional de Ciencia y Tecnología, CONACYT) with project number CONACYT-278608. In this project, we collaborate with UNAM-Sisal and CINVESTAV-Mérida.